Structuring international financial support for climate change mitigation in developing countries - Karsten Neuhoff; Sam Fankhauser; Emmanuel Guerin; Jean Charles Hourcade; Helen Jackson; Ranjita Rajan; John Ward (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In the Copenhagen Accord of December 2009, developed countries agreed to provide start-up finance for adaptation in developing countries and expressed the ambition to scale this up to 100 billion per year by 2020. The financial mechanisms to deliver this support have to be tailored to country and sector specific needs so as to enable domestic policy processes and self sustaining business models, and to limit policy risk exposure for investors while complying with budgetary constraints in OECD countries. This paper structures the available financial mechanisms according to the needs they can address, and reports on experience with their application in bilateral and multilateral settings.
Keywords: F30; G20; R38; 330; Financial mechanism; risk guarantee; development; climate policy; Klimaschutz; Entwicklungshilfe; Entwicklungsfinanzierung; Länderrisiko; Bürgschaft; Industriestaaten-seitig; Entwicklungsländer